Agricultura familiar camponesa e cooperativismo no Maranhão - Da Silva, Jhonny Santos (Universidade Federal Rural do Rio de Janeiro, 2015)
The work that follows is the result of the discipline of the Territorial Dynamics Master’s degree in Sociospatial Development and Regional. The object study are the peasant cooperatives maranhenses highlighting the south and West where these farmers are organized in a network order to strengthen the struggle in defense of Cerrado and the Amazônia trough another productive logic. The research is of a nature documentary theoretical dialogue between the anthropological thought and Marxism. The reality of family faming in Brasil and also are Maranhão presented in tables and plenty of numbers that reflect the importance these peasants to produce food and the need to rethink our agricultural and agrarian structure. We collect data on how is this relationship and the need for public to watch for such emergencies. Finally, we conclude that is a class conflict that presents itself on other fronts that not only agricultural, but the productive as well.